Analysis of Signal Quality, Voice Service, and Data Access on Telkomsel And Indosat Providers in Pakisjaya District - Arip solehudin; Nono Heryana; Agustia Hananto (Information System; Universitas Buana Perjuangan Karawang, 2022)
Quality in communication is very important in activities in this modern era. It is expected that the expected network quality against network quality is actually not expected. Measurement of network performance is important to refer for users to choose the right operator for service providers to improve the quality of their service Drive Test Method is a method used to measure cellular network performance. The purpose of this study is to study the results of research between service providers. The parameters used in this analysis are Receive Signal Code Power (RSCP), Cell ID, Signal Noise Ratio (SNR), Upload Rate, and Download Rate. This parameter is used for the measurement process of the Drive Test method. While the tool used to collect the value of each Drive Test parameter by using an Android-based application, GNet Track Pro. The measurement results with GNet Track Pro are then processed with the Google Earth application as a measurement area. Research data collected in this analysis were 60 cases, with each village 20 data collected to continue processing with the Drive Test method. In this study, Telkomsel chose to excel in voice services with 150 successful numbers of 150 attempted calls. While Indosat excels in providing data access services and special signals in the village of Tanjungbungin.